SYSTEM OF PSYCHOLOGICAL ASSISTANCE IN SELF-REALIZATION OF THE PERSONALITY OF THE ATHLETES: DOMESTIC AND FOREIGN APPROACH - Sokolovskaya, S.V.; Ulyaeva, L.G.; Ulyaeva, G.G.; Orlova, E.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to study domestic and foreign approaches to the system of psychological assistance in the self-realization of the athlete's personality at the stages of many years of sports training. Methods and structure of the study. The study of the features of the psychological support system in the self-realization of the athlete's personality was carried out by theoretical analysis of scientific, methodological and practical publications of the experience of sports psychologists, the study of web resources for the device of the psychological assistance system on the example of such leading countries as Russia, USA, Germany, Great Britain, Italy, Canada , Japan. Results and conclusions. Compared to Russia, athletes, parents and coaches abroad have more access to professional support from a sports psychologist. They have the opportunity to choose for themselves the specialist who is most interesting, for example, in terms of education and competence in sports psychology. To solve the identified problems, the NPO "Association of Sports Psychologists" (ASP), developed a project aimed at creating a system of scientific and methodological support for the professional activities of sports psychologists, educational and educational support, and assistance in creating jobs.